(28b-1)-9(3b+1)=-2

Simple and best practice solution for (28b-1)-9(3b+1)=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (28b-1)-9(3b+1)=-2 equation:


Simplifying
(28b + -1) + -9(3b + 1) = -2

Reorder the terms:
(-1 + 28b) + -9(3b + 1) = -2

Remove parenthesis around (-1 + 28b)
-1 + 28b + -9(3b + 1) = -2

Reorder the terms:
-1 + 28b + -9(1 + 3b) = -2
-1 + 28b + (1 * -9 + 3b * -9) = -2
-1 + 28b + (-9 + -27b) = -2

Reorder the terms:
-1 + -9 + 28b + -27b = -2

Combine like terms: -1 + -9 = -10
-10 + 28b + -27b = -2

Combine like terms: 28b + -27b = 1b
-10 + 1b = -2

Solving
-10 + 1b = -2

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 1b = -2 + 10

Combine like terms: -10 + 10 = 0
0 + 1b = -2 + 10
1b = -2 + 10

Combine like terms: -2 + 10 = 8
1b = 8

Divide each side by '1'.
b = 8

Simplifying
b = 8

See similar equations:

| 19x+4+26x-4=180 | | y/4-6=-9 | | 12-4(2x+3y)= | | 6/d=3 | | 8v-5+1=-4 | | 240-83x=541 | | 3x+41-5x=3-8x+2 | | 1/4x+1/4x=8 | | k+4(2k-7)=-100 | | (3/4)/(5/7) | | 2-5p-3p=-6 | | 3/4/5/7 | | -2m-24=0 | | 2-5p-4p=-6 | | 48/60 | | y+1=6/5x+18/5 | | a+4+2a=-8 | | -8n+-4=-28 | | (-3)*(-13)+(-41)= | | -11+2(x-3)+x=3(x-3)-8 | | 1=2+1/2 | | 5(3x+2)=2(2x+3) | | 5(x-2)-3=2x+3(-3+x) | | -5(7+7n)=-280 | | x/2+6=3x-12+x/2 | | 12x+15=-2 | | 3x+7=6x+9 | | 8n-4=-28 | | -6x-2x=-8 | | Y-2=4/9(x-3) | | 5x+5+1=-9 | | b+7+6=19 |

Equations solver categories